2014
DOI: 10.1002/jso.23657
|View full text |Cite
|
Sign up to set email alerts
|

Breast conserving therapy for DCIS—Does size matter?

Abstract: The incidence of ductal carcinoma in situ has increased dramatically with the use of screening mammography. Most patients can be considered for breast conserving therapy, depending upon patient and pathologic variables. In addition to other factors, tumor size is important to provide proper patient selection for breast conserving surgery and predict risk of local recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 68 publications
(82 reference statements)
1
8
1
Order By: Relevance
“…On univariate competing risk analysis, the risk of IBTR was significantly higher when the index DCIS was diagnosed at a younger age, presented clinically, and of large size or of 3+ HER2 status, consistent with previous studies. 32,33 However, the lower rates of IBTR compared with CBC after BCS for DCIS patients whose margin was negative by the polygon method observed in our study are in sharp contrast with those in prior literature that consistently showed higher rates of IBTR than CBC following BCS with or without radiotherapy. According to the National Surgical Adjuvant Breast and Bowel Project study reported by Fisher et al, in the lumpectomy alone group, 16.3% (64/391) women developed IBTR whereas 2.0% (8/391) women developed CBC.…”
contrasting
confidence: 99%
“…On univariate competing risk analysis, the risk of IBTR was significantly higher when the index DCIS was diagnosed at a younger age, presented clinically, and of large size or of 3+ HER2 status, consistent with previous studies. 32,33 However, the lower rates of IBTR compared with CBC after BCS for DCIS patients whose margin was negative by the polygon method observed in our study are in sharp contrast with those in prior literature that consistently showed higher rates of IBTR than CBC following BCS with or without radiotherapy. According to the National Surgical Adjuvant Breast and Bowel Project study reported by Fisher et al, in the lumpectomy alone group, 16.3% (64/391) women developed IBTR whereas 2.0% (8/391) women developed CBC.…”
contrasting
confidence: 99%
“…The histologic diagnosis of DCIS is commonly made by examination of core‐needle biopsy, followed by excision and definitive pathologic examination. Approximately 25% of lesions diagnosed as DCIS on core biopsy will be found to also include invasive carcinoma after surgical resection; factors associated with the finding of invasive cancer include larger lesion size, intermediate or high nuclear grade, and negative hormone receptor status . Because of the potential for finding invasive disease, the National Comprehensive Cancer Network (NCCN) guidelines recommend that sentinel lymph node biopsy (SLNB) be considered for patients to be treated with mastectomy or with excision in an anatomic location (eg, tail of the breast) that could compromise the performance of a future sentinel lymph node biopsy…”
Section: Methodsmentioning
confidence: 99%
“…Size may be difficult to measure, because DCIS often involves the ductal system in a complex, 3‐dimensional branching pattern. Positive or close surgical margins are associated with a higher risk of recurrence, and some women who undergo BCS require reexcision to achieve clear margins . In addition to having prognostic significance, ER status is important because tamoxifen therapy is an option for women with ER‐positive tumors to decrease the risk of recurrence or to prevent second primary breast cancers from developing.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A wide range of recurrence rates is reported in the literature due to variable follow up times and the use of adjuvant radiation. [4][5][6][7] Other factors that influence recurrence rate include patient age, presentation as a palpable mass, nuclear grade of the DCIS, margin status at the time of excision in cases of breast conservation, and the extent of DCIS. Each of these are statistically significant independent prognostic factors, some of which are used in combination to generate the University of Southern California/Van Nuys Prognostic Index (USC/VNPI), a numeric score used to help guide clinicians regarding the need for radiation with breast conservation.…”
Section: Introductionmentioning
confidence: 99%